2012
DOI: 10.1002/pssb.201147334
|View full text |Cite
|
Sign up to set email alerts
|

CO adsorption on metal‐oxide surfaces doped with transition‐metal adatoms

Abstract: Using first principles density functional theory calculations, we have studied the adsorption of carbon monoxide (CO) on clean, Ag and Pd doped MgO(001), TiO 2 (110), and a-Al 2 O 3 (0001) surfaces. Our results show that adsorption of CO on the clean surfaces is generally weak. Ag doping improves the adsorption only weakly, except on the TiO 2 surface. The presence of Pd, however, significantly improves adsorption on all the surfaces studied. On the doped surfaces, the best adsorption sites are always the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Whereas the refilling of the oxygen vacancies in reducible oxides such as CeO x stimulates the oxygen dissociation on the oxide-island adjacent surface sites, this is not the case for SiO 2 . In turn, the spillover of CO from the SiO 2 islands (a weakly bound mobile CO layer can be formed on the SiO 2 surface [35]) supports the interpretation that the regions around the SiO 2 islands must be rather inactive for the CO oxidation.…”
Section: Resultsmentioning
confidence: 82%
“…Whereas the refilling of the oxygen vacancies in reducible oxides such as CeO x stimulates the oxygen dissociation on the oxide-island adjacent surface sites, this is not the case for SiO 2 . In turn, the spillover of CO from the SiO 2 islands (a weakly bound mobile CO layer can be formed on the SiO 2 surface [35]) supports the interpretation that the regions around the SiO 2 islands must be rather inactive for the CO oxidation.…”
Section: Resultsmentioning
confidence: 82%
“…In a work focusing on the adsorption of CO onto a-Al 2 O 3 (0001) and onto Pd and Ag deposited on a-Al 2 O 3 (0001) it was found that adsorption is preferred on the metal and not on the surface site adjacent to the metal. 58 This was not due to the larger adsorption energy of CO on Ag deposited on a-Al 2 O 3 (0001) (E a CO on Ag/a-Al 2 O 3 (0001) = 0.6 eV and E a CO on a-Al 2 O 3 (0001) = 0.53 eV) but mainly because of the structural effects. Similar observations related to energy differences were found for Au/ Al 2 O 3 although with subtle differences.…”
Section: The Hydroxylated (0001) Surface Of A-al 2 Omentioning
confidence: 96%
“…Very recently, Blomqvist et al 86 used generalized gradient approximation (GGA) in combination with plane wave basis set to study CO and transition metal (Ag and Pd) ad-atom co-adsorption on the α-Al 2 O 3 (0001) surface. The estimated binding energy of CO was −11.53 kcal/mol (independently of the surface site) in good agreement with the value of −12.97 kcal/mol determined in this work.…”
Section: Co Adsorption On Undoped and Fe3+ And Cr3+ Doped α-Al2o3 (00mentioning
confidence: 99%